An experiment on how graduating students represent software designs - Moreno, Silvana; Vallespir, Diego; Solari, Martin (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20963, 2022)
As a practice, software design seeks to contribute to developing quality software. For graduating students, the design is difficult to understand, and building a good design seems to require a certain level of cognitive development. In this study, we report an experiment to know how students habitually represent detailed design (what artifacts and ways of design representation they use) and if there is an effect on software quality when they deliver the design representation. We found that students design on a basic level, they do not achieve complete designs that combine several artifacts to model dynamic and static aspects. Also, the delivery of design representation did not improve software quality.